Improving Indoor Air Quality in Classrooms via Wind-Induced Natural Ventilation. (10th June 2021) - Bayoumi, Mohannad
Abstract : Student performance in classrooms is related to the indoor environmental quality. High air change rates are necessary to secure an acceptable level of indoor air quality and provide fresh air, which require large amounts of energy and technical installations. Mostly, mechanically supplied air is partially mixed with the return air. In warm climates, the capacity for natural ventilation is not fully exploited in modern buildings. During periods of acceptable outdoor temperatures, buildings need to adapt and employ available free renewable resources, such as wind. In this context, the building form, orientation, and envelope openings are crucial to enable an increased air change rate, user satisfaction, and energy savings. Owing to the difficulty of providing cross-ventilation in buildings with double-loaded corridors, single-sided ventilation is the most common approach. This study investigates the methods to improve the wind-driven air exchange of classrooms in warm climates, where naturally ventilated corridors help increase air movement. This study examines the potential of a set of alternatives within the context of a generic model regarding the pressure distribution, thermal sensation, air velocity, and air change rate. The study suggests that no single opening scenario can be applied to all façades at any time. Each façade requires special treatment. Decisions on natural ventilation need to be made during the early design stages for each façade. It was found that with the aid of low-tech modifications, remarkable increases in air change rates, in some cases up to 14.5 times that of the typical single-sided ventilation case, could be achieved.